A Brand-New Metal Complex Catalyst-Free Approach to the Synthesis of 2,8-Dimethylimidazo[1,2-b]pyridazine-6-Carboxylic Acid—A Key Intermediate in Risdiplam Manufacturing Process - Georgiy Korenev; Alexey A. Gutenev; Fyodor V. Antipin; Vladimir V. Chernyshov; Maria P. Korobkina; Maxim B. Nawrozkij; Roman A. Ivanov (Molecules, 2025)
In this study, we report for the first time a brand-new protocol for the multigram-scale synthesis of 5-methyl-6-oxo-1,6-dihydropyridazine-3-carboxylic and 2,8-dimethylimidazo[1,2-b]pyridazine-6-carboxylic acids, without the utilization of metal-complex catalysts. The developed technology for the production of the aforementioned acids is of great importance for two reasons. Firstly, these acids serve as intermediates in the synthesis of risdiplam, the first small-molecule drug approved for the treatment of spinal muscular atrophy. Secondly, they themselves are valuable building blocks right from a broader medicinal chemistry perspective. The synthesis of risdiplam was carried out using a modified synthetic protocol, utilizing the acids indicated above as the key intermediates. The protocols presented in this study enable the production of target compounds with high purity and an acceptable yield.